E-commerce Delivery: Which Links with the Consumer? - Alaa Eddine El Moussaoui; Brahim Benbba; Zineb El Andaloussi (International Journal of Supply Chain Management, 2021)
In recent years, the topics of urban logistics and consumer behavior have attracted considerable interest from researchers and practitioners. As cities rapidly urbanize and customer service expectations increase, the corpus of research on these topics has become fragmented. The problems of urban logistics have become a widespread area for supply chain companies, due to the growth of e-commerce which allows consumers to design personalized packages, at the location of their choice. This means that consumers can both set the quality standards for delivery and control the performance of e-commerce. The aim of this article is to answer the following questions: (1) How are new consumption patterns changing the logistical pattern of cities? (2) How does e-commerce delivery relate to the final customer? This will give practitioners and researchers an overview of recent theoretical approaches in order to analyze the development of the discipline and provide directions for future research.